2021
DOI: 10.1002/lio2.598
|View full text |Cite
|
Sign up to set email alerts
|

Topical mitomycin C application post endoscopic removal of antrochoanal polyp

Abstract: Objective Assessment the effect of topical application of mitomycin‐C (MMC) after endoscopic removal of antrochoanal polyp (ACP) on its recurrence rate. Methods This prospective study was done on patients with ACP. Endoscopic nasal surgery has been done to remove the polyp after wide middle meatal antrostomy. The patients were categorized into two groups. In MMC group, after endoscopic ACP removal, MMC on a piece of cotton was topically applied inside the maxillary antrum in the suspected site of ACP origin. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…El-Sharkawy [ 8 ] reported that 38.9% were located in the posterior and lateral walls, 36.1% in the medial wall, and 8.3% in the inferior wall. Some scholars found that 7/12 were in the inferolateral wall, while 2/12 were in the inferomedial and superomedial walls, and 1/12 were in the margin of the ostium [ 9 ]. In this study, the ACP was located in the inferomedial wall in 35.79%, in the inferolateral wall in 23.16%, in the inferior wall in 14.74%, and in the anterior wall in 10.53%.…”
Section: Discussionmentioning
confidence: 99%
“…El-Sharkawy [ 8 ] reported that 38.9% were located in the posterior and lateral walls, 36.1% in the medial wall, and 8.3% in the inferior wall. Some scholars found that 7/12 were in the inferolateral wall, while 2/12 were in the inferomedial and superomedial walls, and 1/12 were in the margin of the ostium [ 9 ]. In this study, the ACP was located in the inferomedial wall in 35.79%, in the inferolateral wall in 23.16%, in the inferior wall in 14.74%, and in the anterior wall in 10.53%.…”
Section: Discussionmentioning
confidence: 99%